The Models of Character and Akhlaq Education for Special Needs Children in An Inclusion School - Drajat, Manpan; Mohd Nor, Mohd Roslan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
The law stresses that education is the right of all citizens, including children with special needs. The need for education is the same as school-age children in general, but the training provided is adjusted to the specifics of the children. It is certainly guaranteed that all children need character education and akhlaqul karîmah. This research aims to explore how character education and akhlaq in children with special needs in Al-Ghazali Jatinangor Inclusion Elementary School. The method used is phenomenological quality research. The data is collected in by observations, interviews, documentations, and Focus Group Discussion (FGD). Then, it was analyzed using interactive analysis techniques. The results indicate that the education program at Al-Ghazali Inclusion Elementary School is different from most other elementary schools. It has long hours of teaching and learning activities and most of the students’ time conducted at school activities are filled with daily routines that build consistent characters and akhlaqul karîmah for the students. Undang-undang menegaskan bahwa pendidikan adalah hak semua warga termasuk anak berkebutuhan khusus. Kebutuhan akan pendidikan anak berkebutuhan khusus sama dengan anak usia sekolah pada umumnya, akan tetapi pendidikan yang diberikan tentu disesuaikan dengan kekhususan anak tersebut. Namun dapat dipastikan bahwa semua anak termasuk anak berkebutuhan khusus membutuhkan pendidikan karakter dan akhlak mulia. Penelitian ini bertujuan untuk mengeksplorasi bagaimana pendidikan karakter dan akhlak pada anak berkebutuhan khusus di Sekolah Dasar (SD) Inklusi Al-Ghazali Jatinangor Sumedang. Metode yang digunakan penelitian ini adalah penelitian kualitatf fenomenologi. Data penelitian ini dikumpulkan dengan observasi, wawancaran, dokumentasi dan Focus Group Discussion (FGD). Data dianalisis dengan teknik interactive analysis. Hasil penelitian ini menunjukkan bahwa program pendidikan di SD Inklusi Al-Ghazali Jatinangor ini berbeda dengan kebanyak SD lainnya yaitu jam kegiatan yang panjang yang sebagian besar waktu kegiatan di sekolah diisi dengan daily routin yang membangun karakter dan akhlak mulia yang dilakukan secara konsisten, baik untuk anak normal mupun anak berkebutuhan.